2019
DOI: 10.3324/haematol.2018.210146
|View full text |Cite
|
Sign up to set email alerts
|

Rapid growth is a dominant predictor of hepcidin suppression and declining ferritin in Gambian infants

Abstract: Iron deficiency and iron deficiency anemia are highly prevalent in low-income countries, especially among young children. Hepcidin is the major regulator of systemic iron homeostasis. It controls dietary iron absorption, dictates whether absorbed iron is made available in circulation for erythropoiesis and other iron-demanding processes, and predicts response to oral iron supplementation. Understanding how hepcidin is itself regulated is therefore important, especially in young children. We investigated how ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 55 publications
4
48
0
Order By: Relevance
“…A recent study of Armitage et al indeed observed that antecedent weight gain was negatively associated with serum hepcidin levels in Gambian infants. 39 However, the virulence of infectious organisms depends on their ability to assimilate iron from their host.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study of Armitage et al indeed observed that antecedent weight gain was negatively associated with serum hepcidin levels in Gambian infants. 39 However, the virulence of infectious organisms depends on their ability to assimilate iron from their host.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses were stratified by sex because of sex-specific differences in hepcidin levels and iron homeostasis that have been described earlier. 20,26,27,30,38,39 SPSS version 22 was used for data analysis.…”
Section: Males Femalesmentioning
confidence: 99%
See 1 more Smart Citation
“…To gain greater insight into how hepcidin levels are regulated and affected by different factors in a primary care setting, and how these change in early infancy over time, Armitage and co-workers analyzed data from two birth cohorts in The Gambia, Western Africa, adopting a longitudinal approach to the analysis. 15 They took repeat measurements of serum concentrations of hepcidin, iron, the iron storage protein ferritin, and soluble transferrin receptor (sTfR) (which is a marker for the needs of iron for erythropoiesis) and studied the results for associations of these markers with birth weight, growth, seasonality, infection, anemia, and nutrition. Children were investigated from birth until one year of age.…”
mentioning
confidence: 99%
“…However, such faster growing children are more likely to become iron deficient because dietary iron availability cannot compensate for the increased incorporation of iron in the body. Thus, such children need specific attention in order to avoid unwanted negative effects of iron deficiency on their development from one year of age onwards; based on the data presented by Armitage et al, 15 these infants can be identified by low hepcidin levels at the age of 12 months, but this also predicts that they will respond to oral iron therapy.…”
mentioning
confidence: 99%